Auditory Processing in People with Chronic Aphasia - Pavičić Dokoza, Katarina; Kolundžić, Zdravko (Collegium antropologicum, 2020)
The preconditions for successful voice communication are good hearing and listening, and auditory processing that includes the ability to process the audio signal. Damage or deceleration of sound signal processing at any level from the periphery to the central structures leads to disintegration and inability to process the signal effectively. Auditory processing in people with aphasia has not been examined in Croatia to date. Results of studies conducted in other languages point to negative effects of auditory processing difficulties on the receptive and expressive component of the language. This study was conducted on a sample of subjects with chronic aphasia and a group of control subjects with no neurological or any other disorders that can affect auditory processing. The inclusion criteria for persons with aphasia were impaired language skills as a result of cerebrovascular accident that occurred at least six months before the examination, regardless of severity and type of aphasia and normal hearing status. The study did not include persons with aphasia who were unable to repeat the six-word sentence, due to impaired comprehension or speech expression, and those whose comprehension was not sufficient to cooperate well during the test. The test was conducted individually for 30 minutes per subject using the Auditory processing test (PSP) that is standardized for the Croatian language. Results from this study showed statistically significant lower achievement on all subtests on PSP-1 (filtered words, speech in noise, dichotic words test, and dichotic sentence test) in people with aphasia compared with the control group. People with aphasia and control group subjects showed better results in favor of the left ear on variable speech in noise. Filtered words were easily processed through the left ear in people with aphasia while dichotic sentences were easily processed through the left ear in the control group. The results of this study confirm the hypothesis of the presence of auditory processing difficulties in people with aphasia and are consistent with previous studies conducted in other languages. In addition, the study points to the need of introducing specific therapeutic procedures in rehabilitation in order to improve the function of auditory processing in persons after a cerebrovascular accident. Preduvjeti uspješne govorne komunikacije su dobar sluh i slušanje, te slušno procesiranje koje uključuje sposobnost obrade zvučnog signala. Oštećenja ili usporavanja obrade zvučnog signala na bilo kojoj razini od periferije do središnjih struktura dovodi do dezintegracije i nemogućnosti učinkovite obrade signala. U Hrvatskoj do sada nije ispitivano slušno procesiranje kod osoba s afazijom. Rezultati istraživanja provedenih u drugim jezicima upućuju na negativan utjecaj poremećaja slušnog procesiranja na receptivnu i ekspresivnu sastavnicu jezika. Istraživanje je provedeno na uzorku ispitanika s kroničnom afazijom i skupini kontrolnih ispitanika bez neuroloških ili drugih bolesti koje mogu utjecati na slušno procesiranje. Kriteriji uključivanja osoba s afazijom su bili sljedeći: slabije jezične sposobnosti kao posljedica CVI koji se dogodio najmanje šest mjeseci prije ispitivanja bez obzira na težinu i vrstu afazije te uredan sluh. U istraživanje nisu uključene osobe s afazijom koje nisu bile u mogućnosti za ispitivačem ponoviti rečenicu od šest riječi, bez obzira radi li se o poremećaju razumijevanja ili govorne ekspresije, te osobe kod kojih razumijevanje nije bilo dovoljno za dobru suradnju tijekom provođenja testa. Ispitivanje je provedeno individualno u trajanju od tridesetak minuta po ispitaniku pomoću testa PSP-1 koji je standardiziran za hrvatski jezik. Dobiveni rezultati pokazuju statistički značajno slabija postignuća na svim subtestovima Testa slušnog procesiranja (filtrirane riječi, govor u buci, dihotički test riječi, dihotički test rečenica) kod osoba s afazijom u odnosu na kontrolne ispitanike. Osobe s afazijom i skupina kontrolnih ispitanika pokazuju statistički značajne razlike u smislu boljih rezultata na lijevom uhu na varijabli govor u buci. Filtrirane riječi su osobe s afazijom bolje procesirale na lijevo uho dok su kontrolni ispitanici na lijevo uho bolje procesirali rečenice na subtestu dihotički test rečenica. Rezultati potvrđuju hipotezu o prisustvu poremećaja slušnog procesiranja kod osoba s afazijom i u skladu su s ranije provedenim istraživanjima na drugim jezicima. Osim toga, ukazuju na potrebu uvođenja specifičnih terapijskih postupaka u rehabilitaciji u cilju poboljšanja funkcije slušnog procesiranja kod osoba nakon moždanog udara.